Global well-posedness of 3D magneto-micropolar fluid equations with mixed partial viscosity. (February 2017) - Wang, Yinxia; Wang, Keyan
Abstract: In this paper, we investigate the initial value problem for the three dimensional magneto-micropolar fluid equations with mixed partial viscosity. Global existence of smooth solutions are established by energy method, provided that the H 1 norm of the initial value is suitably small.